Spectral response of marine submerged aquatic vegetation: A case study in Western Australia coast - Tin, H.; O'Leary, Mick; Fotedar, Ravi; Garcia, R. (2016)
© 2015 MTS.Marine submerged aquatic vegetation (SAV) plays a vital role as habitats, nursery and feeding grounds for a wide range of marine aquatic and terrestrial life. Recently, remote sensing techniques have been successfully applied in marine benthic mapping in coastal waters. However, the majority of these techniques have focused on either seagrasses meadows or coral reefs. There are a few studies that have been published validating a methodology for mapping SAV on brown macroalgae (Sargassum spp., Ecklonia spp.), seagrasses, and/or other macroalgae groups by spectral response from remote sensing. Hence, we studied the in-situ optical properties of living macroalgae, seagrasses, and rubble. The spectral characteristics of varied SAV groups were measured using the high resolution FieldSpec® 4 Hi-Res portable spectroradiometer. The study site selected was the Shoalwater Islands Marine Park, Rockingham, Western Australia as it is one of the fifteen biodiversity hotspots in Australia. Correlation and Principle Component Analysis were employed to evaluate the differences between SAV groups. The results have documented the spectral features of SAV and their associated habitats in Shoalwater Islands Marine Park, Western Australia, and developed a spectral library to distinguish among seagrass species and algae groups (green, red, and brown benthic macroalgae). The implications of this study will contribute to estimate and detect the distribution and seasonal variation of SAV on a broader scale.